Acesso à rede de cuidados em saúde da pessoa com deficiência em um município de fronteira - Issa, Fatima Moustafa (2022)
The Care Network for People with Disabilities, established in 2012, based on the “Living Without Limits” program, aimed to expand access and improve the provision of care to people with disabilities. In June 2018, Foz do Iguaçu, a triple-border county (Brazil – Paraguay – Argentina), was awarded with the implementation of a Level IV Specialized Rehabilitation Center, covering the micro-region, composed of nine counties of the Ninth Health Regional (9th RS). This study sought to analyze access to the Health Care Network for People with Disabilities in a border town. This was a descriptive study, with a quantitative and qualitative approach. The quantitative collection was based on the Health Management System of the Municipal Health Department of Foz do Iguaçu, and the variables dealt with the sociodemographic and epidemiological profiles of the users. All users attended at the Specialized Rehabilitation Center since 2018, when the service was implemented, were considered as the study population. The collected data were entered in a spreadsheet in the Microsoft Office Excel® software, in a structured instrument with variables organized as follows: sex, age group, skin color/race and rehabilitation modality, and the bivariate analysis was performed using the chi-square test as well as Poisson regression, considering a significance level of 5%. For the qualitative study, 11 workers and 14 service users were interviewed. Data collection followed a semi-structured script by category of respondents, based on a guiding question. For data analysis, the Collective Subject Discourse, developed by Lefèvre and Lefèvre, was used. It was found that, between 2018 and 2021, 125,857 users were served, with a predominance of males (59.3%), aged up to 18 years (47.6%). Physical rehabilitation was the one that stood out the most, followed by auditory, intellectual, and finally visual. Most users (69.6%) needed more than one type of rehabilitation, not being counted in the single modalities. According to the qualitative approach, the disarticulation of the levels of care was observed, with specialized services in rehabilitation as care centralizers. There are workers committed to creating bonds and improving the provision of care and satisfied users, satisfied with the provision of care received, but a municipality still lacking in the provision of access and accessibility to this population. For a system to function in an integrated manner on the frontier, it is necessary to legitimize all the knowledge involved in this construction, to make the thought that all life matters unanimous, to understand the urgency of creating public policies that include all forms of existence and not to allow a society governed by a power that controls and defines the way of being “normal”, and therefore to ensure the continuity of care for people with disabilities, with the reduction of bureaucracy in access to the border population and foreigners.